Perception and Level of Awareness of Child Abuse Among Women in Okabere Community - Blackie Okosun Hassan; Blackie Funmilayo Faustina; Edebiri Ogbemudia Endurance; Olukayoden Seun Bidemi; Abel Odosa Pamela (International Journal of Public Health, 2025)
Child abuse is a significant public health problem with long-lasting impacts on the physical, emotional, and psychological growth of children. Perception and awareness of child abuse among women in Okabere Community, Benin City, Edo State, Nigeria, were examined. A descriptive cross-sectional study design was used, and the data were collected from 133 women using a structured questionnaire. Findings revealed that 82% of the respondents were aware of child abuse, and 62.4% quoted schools and 20.3% places of worship as sources of information. Most were aware of sexual (28.6%) and physical abuse (21.8%) more than emotional abuse (17.3%) and neglect (14.3%). Perception was influenced by socio-cultural as well as economic influences because 60.2% quoted cultural beliefs and 80.5% blamed poverty for abuse. While almost all of the participants agreed that child abuse was a serious issue (80.5%), only 47.4% engaged in prevention activities. Community education, culturally targeted interventions, and women's empowerment are urgently needed for the prevention of child abuse in rural areas, as the study suggests.